Tiger Conservation Initiatives in Nepal - Karki, Jhamak Bahadur; Jnawali, Shanta Raj; Gurung, Ghana; Pandey, Megh B; Upadhyay, Gopal P (The Initiation, 2011)
Tiger (Panthera tigris tigris) is an icon of Asia’s natural heritage and ecological integrity. Tiger along with one-horned rhinoceros (Rhinoceros unicornis) and wild elephant (Elephas maximus) in the lowlands and snow leopard (Uncia uncia), musk deer (Muschus sp.) in mountain have been serving as a flagship species to derive worldwide conservation attention not only to benefit them but also to facilitate the survival of other associated species. However, their number is decreasing rapidly. Owing to this, various initiatives have been taken both at national and international level. This article reviews about the different initiatives taken so far and the ways forth. DOI: http://dx.doi.org/10.3126/init.v4i0.5537 The Initiation Vol.4 2011 56-68